Rockonomics : how the music industry can explain the modern economy - Krueger, Alan B., 1960-2019 (London : John Murray, 2020)
'An entertaining guide to economics by a former adviser to Barack Obama that uses the lessons of the music business to explain what is happening in the rest of the world' The Times, Books of the Year 'A key voice on a vast array of economic issues for more than two decades' Barack Obama 'An absolutely brilliant mind. The definition of left and right brain balance' Quincy Jones 'The music business keeps re-inventing itself (from records, to tape, to CDs to streaming) and Alan Krueger covers all the bases. As one former LSE student once sang: 'its only rock and roll but I like it, like it, yes I do.' That applies to this book too' Richard Thaler, Nobel Prize Recipient and author of 'Nudge' 'Rockonomics is entertaining, educational and enlightening. Alan Krueger gives us a backstage tour of the music industry - and in doing so, he creates a brilliant metaphor for our entire economy. Highly recommended' Harlan Coben Alan Krueger, the former chairman of the president's Council of Economic Advisers, uses the music industry, from rock artists to music executives, from managers to promoters, as a way in to explain the principles of economics, and the forces shaping our economic lives. The music industry is often a leading indicator of today's economy; it is among the first to be disrupted by the latest wave of technology, and examining the ins and outs of how musicians create and sell new songs and plan concert tours offers valuable lessons for what is in store for businesses and employees in other industries that are struggling to adapt. Drawing on interviews with leading band members, music executives, managers, promoters, and using the latest data on revenues, royalties, tour dates, and merchandise, Rockonomics takes readers backstage to show how the music industry really works - who makes money, how the economics of the music industry has undergone a radical transformation during the last twenty years, and what this tells us about our wider economy today.
Keywords: Economy